A Rare Case of Primary Cutaneous Follicle Center Lymphoma Mimicking Leprosy - Made, Marlina; Tabri, Farida; Ilyas, Faridha; Waspodo, Nurelly; Rimayani, Sri; Kadir, Dirmawati (Open Access Macedonian Journal of Medical Sciences, 2022)
Cutaneous B-Cell Lymphoma is a rare type of cutaneous lymphoma with a plethora of clinical manifestations ranging from macules, papules, nodules, or plaques. The lesions are often painless and certain subtypes such as the primary cutaneous follicle center lymphoma (PCFCL) are indolent. The disease is often misdiagnosed with other dermatoses including bacterial and fungal infections. Here we report a 55-year-old female patient with clinical manifestations resembling multibacillary leprosy that was then confirmed to be PCFCL through aid of dermoscopy and histopathology. The patient then undergone chemotherapy using the R-CHOP regiment which resulted in significant clinical improvement and no signs of metastases or extracutaneous involvement upon follow-up.